MODELAGEM MATEMÁTICA NO PROCESSO DE ENSINO E APRENDIZAGEM DA MATEMÁTICA NO ENSINO FUNDAMENTAL: AÇÕES E INTERAÇÕES - Komar, Marcelo Fabricio Chociai (2017)
The present work presents aspects of Mathematical Modelling in Mathematics Education, capable of being an alternative to the teaching and learning processes of Mathematics in the scope of Basic Education of Basic Education. The focus of our research focused on the following question: What elements of Mathematical Modelling, in the conception of Mathematics Education, are constituted in the teaching and learning processes of Elementary School students? The general objective is to establish Modelling as a teaching and learning methodology of Mathematics, based on the analysis of the elements provided by the actions and interactions of the students and teacher, in the development of Modelling activities. From the general objective we delimit the specific objectives: to identify and to analyze pedagogical, psychological and behavioral aspects perceived in the students when involved in the activities of Mathematical Modelling. Also observe to what extent the teacher's attitude favors learning involving Mathematical Modelling. For the fulfillment of the question and objectives this research is conceived in the qualitative/interpretive perspective, with a design from the perspective of Lüdke and André (1986). The treatment of the data follows the perspective of Bogdan and Biklen (1994). In this outline we intend to understand, from the collected data, from the point of view of the teacher, the possibility of the teacher researching the teaching process, and from the perspective of the students, actions and procedures able to favor the learning of the mathematical contents and learning of other fields of knowledge, since they may indicate ways and strategies and suggest questions that benefit the student to take an active role in the construction of their knowledge, previously treated in a Cartesian and traditional way. The results of this research point out that Mathematical Modelling, from the perspective assumed, allows for the capacity to develop autonomy resulting from the action of thinking, reflecting, searching for data, raising and finding solutions to the problems provided by data collection, in relation to the chosen theme. The interaction between the participants, teachers and students, has proved to be a potentiating element in the development of activities and learning, both in mathematical content and in other non-mathematical aspects related to the development of a theme, providing the development of actions that critical and reflective thinking of students.